Detailed description of larvae and pupae of two Neotropical species of Alluaudomyia Kieffer (Culicomorpha: Ceratopogonidae) - Diaz, Maria Florentina (2015)
The first description of the larva and pupa of Alluaudomyia amazonica Spinelli & Wirth and a detailed redescription of the larva and pupa of A. schnacki Spinelli are provided. Studied specimens were collected in the Corrientes and Buenos Aires provinces, Argentina, from habitats associated with aquatic ferns, those of A. amazonica with Salvinia biloba Raddi emend. De la Sota and A. schnacki with Azolla filiculoides Lam. The larvae were examined using a Scanning Electron Microscope (SEM) and a Compound Microscope (CM), while the pupae by the CM only. Data on the bionomics of both species are provided.